2012
DOI: 10.4236/health.2012.44034
|View full text |Cite
|
Sign up to set email alerts
|

Osteoma of mastoid process obstructing external auditory canal: A case report

Abstract: Objective: To discuss the surgical treatment of recurrent osteoma of the mastoid process of the temporal bone, that obstructed external auditory canal causing unilateral conductive hearing loss. Setting: The study was carried out in ENT Clinic, University Clinical Center of Kosovo, Prishtina, Kosovo. Design: Retrospective review of a clinical case. Patient, Intervention and Result: We treated surgically with success a 14-year-old boy with osteoma of mastoid process, obstructing the external auditory canal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It is reported that in cases of osteomas extending into the fallopian canal, complete excision is not indicated since there is risk of damage to the facial nerve [14]. However, it is reported also that partial surgical excision by drilling on the tumor tissue may result in recurrence of tumor that may grow medially to encroach on vital structures making potential future revision excision challenging [14]. The definitive treatment of osteoma remains of complete resection by drilling around the osteoma and avoiding damage to vital structures [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that in cases of osteomas extending into the fallopian canal, complete excision is not indicated since there is risk of damage to the facial nerve [14]. However, it is reported also that partial surgical excision by drilling on the tumor tissue may result in recurrence of tumor that may grow medially to encroach on vital structures making potential future revision excision challenging [14]. The definitive treatment of osteoma remains of complete resection by drilling around the osteoma and avoiding damage to vital structures [15].…”
Section: Discussionmentioning
confidence: 99%